2020
DOI: 10.1038/s41388-020-01466-x
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA BCYRN1 inhibits glioma tumorigenesis by competitively binding with miR-619-5p to regulate CUEDC2 expression and the PTEN/AKT/p21 pathway

Abstract: Glioma is the most common malignant tumor in the central nervous system. Altered long noncoding RNAs (lncRNAs) are playing regulatory roles in physiological and pathogenic processes in cancer. Here, we uncovered a differentially expressed lncRNA called brain cytoplasmic RNA 1 (BCYRN1), and elucidated its function and molecular mechanism in the progression and development of glioma. Three fresh tumor tissues from glioma patients and three normal brain tissues from craniocerebral trauma patients were prepared fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 66 publications
0
68
0
Order By: Relevance
“…The ceRNA network is frequently deregulated in human cancer, which is involved in cancer occurrence, development, and progression [ 10 ]. For example, lncRNA BCYRN1 functioned as a tumor suppressor in glioma by sponging miR-619-5p and elevating CUEDC2, thereby inactivating PTEN/AKT/ p 21 pathway [ 11 ]. LncRNA UCA1 was reported as a driver of Warburg effect and carcinogenesis that sponged and inhibited miR-203 activity, leading to increasing HK2 expression in esophageal cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ceRNA network is frequently deregulated in human cancer, which is involved in cancer occurrence, development, and progression [ 10 ]. For example, lncRNA BCYRN1 functioned as a tumor suppressor in glioma by sponging miR-619-5p and elevating CUEDC2, thereby inactivating PTEN/AKT/ p 21 pathway [ 11 ]. LncRNA UCA1 was reported as a driver of Warburg effect and carcinogenesis that sponged and inhibited miR-203 activity, leading to increasing HK2 expression in esophageal cancer [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“… Mu et al (2020) identified 183 lncRNAs that were significantly differentially expressed in the glioma samples of patients compared with normal control and further investigated the function of lncRNA BCYRN1 (brain cytoplasmic RNA 1, also called BC200) which was the most downregulated one. Functionally, they showed that BCYRN1 overexpression can repress the proliferation and migration of glioma cells, while its knockdown has opposite effects.…”
Section: Examples Of Lncrna–mirna–mrna Cernets In Gliomamentioning
confidence: 99%
“… 30 , 31 , 32 At the same time, some data have indicated that decreased PTEN expression is a common event in HCC and is associated with disease stage, tumor grade and size, and increased expression of tumor markers. 33 , 34 , 35 , 36 …”
Section: Introductionmentioning
confidence: 99%